Misclassification of coronary heart disease in mortality statistics. Evidence from the WHO-MONICA Ghent-Charleroi Study in Belgium. Issue 8 (August 1998) - De Henauw, S; de Smet, P; Aelvoet, W; Kornitzer, M; De Backer, G
Abstract : STUDY OBJECTIVE: To validate the Belgian vital statistics for coronary heart disease (CHD) on the basis of an independent acute myocardial infarction (AMI) register, carried out as part of the WHO-MONICA project. DESIGN: Records of fatal cases of AMI in the WHO-MONICA register were individually linked to the corresponding death certificates. SETTING: Since 1983, the WHO-MONICA Collaborating Centre Ghent/Charleroi registers all fatal and non-fatal AMI in the age group 25-69 years in two geographical areas, Ghent in the northern Dutch speaking part and Charleroi in the southern French speaking part of Belgium. Registration is done according to the MONICA protocol. The official vital statistics in Belgium are published on a yearly basis. They are essentially a reflection of the "underlying" causes of death, coded according to the 9th revision of the International Classification of Diseases (ICD). The study was undertaken in the period 1983-1991. MAIN RESULTS: Out of a total of 741 (Ghent) and 934 (Charleroi) well documented MONICA fatal cases of AMI, 492 (66.4%) and 641 (68.6%), respectively, were officially labelled as CHD (ICD code 410-414); 438 (59.1%) and 385 (41.2%), respectively, were officially labelled as AMI (ICD code 410). A substantial fraction of the MONICA AMI cases–27.1% in Ghent and 38.2% in Charleroi–was coded as "other forms of CHD" (ICD 411-414) or as "other forms of heart disease" (ICD 420-429). The remaining MONICA AMI cases–13.8% in Ghent and 20.6% in Charleroi–were classified in either very aspecific (for example, atherosclerosis, ICD 440) or totally unrelated ICD codes (for example, neoplasm, ICD 140-239). CONCLUSIONS: It is concluded from the results in this paper that a substantial part of all deaths caused by CHD in Belgium are labelled with incorrect ICD codes and are therefore misclassified in the official mortality statistics for Belgium. This is partly caused by a "drainage" of cases towards less specific CHD related ICD categories. A considerable fraction, however, seems to be absolutely misclassified.